Research and Development Buku “Ikhtiar Mengabadikan Cinta Suami dan Istri” Berdasarkan Penelitian Penyebab Perceraian di Kota Yogyakarta - Zubaidah, Syarif; Irfan, Lukman Ahmad (Tapis: Jurnal Penelitian Ilmiah, 2019)
This research was conducted to develop a sakinah family-building instrument through the development of a Buku Bekal Pengantin, which was specifically arranged to overcome the divorcement. The strategy used is by formulating the causes of divorcement occurred then developing an understanding and steps to avoid divorce by involving Judges, Registrars, and parties who are undergoing divorce proceedings in the Yogyakarta City Religious Court. Data collection methods used were interviews and filling in the assessment questionnaire of the books developed. Data analysis of interview data was done by editing, coding, and descriptive analysis, while data from questionnaires were analyzed by average analysis then converted into qualitative assessment results. The results of the feasibility test show that the acceptable of Buku Bekal Pengantin to raise a sakinah family and avoiding divorcement is one that has: First, the book must has a three-part of content structure, namely: Hikayat Suami dan Isteri Mengabadikan Cinta, Alasan Perceraian, Argumetasi Lebih Baik Bertahan, Mengatasi Masalah Keluarga Sejak Dini, Hukum Perceraian, Awal Kesuksesan Hubungan Suami dan Isteri. Second, the content presented is designed to have a soul-boosting element to maintain the marriage relationship by return to Allah. Third, the language writing style must understandabel, and readable.